A Survey Paper On Credit Card Fraud Detection Using Different Classifiers - Kumar, Ashish; Soni, Shivank Kumar; Agrawal, Chetan (International Journal of Computer Sciences and Engineering, 2019)
In this survey we will converse the classification algorithms which are useful on credit card datasets used for finding the scam detection of credit cards. The two major mechanisms to avoid frauds along with losses due to fraudulent actions are fraud avoidance and fraud discovery system. Fraud prevention is the practical mechanism with the objective of disable the incidence of fraud. Fraud discovery systems come interested in play when the fraudsters exceed the fraud prevention scheme and begin a fraudulent transaction. No one can recognize whether a fraudulent transaction has accepted the prevention method. Consequently, the objective of the fraud detection method is to ensure all transaction for the prospect of being fraudulent despite of the prevention method, along with to recognize fraudulent ones as rapidly as probable after the fraudster has begin to commit a fraudulent transaction.